A rare case of azathioprine induced anagen effluvium and plica neuropathica - Rijhwani, Manish; Patel, Meet D.; Malik, Amrit; Nijhawan , Manisha (International Journal of Research in Dermatology, 2024)
Anagen effluvium is a type of hair loss that results from a sudden decrease in the metabolic activity of the hair follicle’s matrix cells. The condition is commonly associated with cancer treatments such as chemotherapy and radiation, but can also be caused by other factors. Plica neuropathica, on the other hand, is a condition where hair on the scalp becomes irreversibly matted. It is often linked to psychiatric disturbances, poor hair care, scalp infestations, and the use of ionic surfactants in shampoos. In rare cases, it has also been associated with certain medications. Here we present a rare case of a 16-year-old female who was on azathioprine and was diagnosed with an overlap of both conditions.